NEW RECORD OF CESTODE GENUS DILEPIS WENILAND, 1858 IN AVIAN HOST LITTLE CORMORANT, MICROCARBO NIGER (AVES: PHALACROCORACIDAE) OF DISTRICT KAMBER-SHAHDADKOT, SINDH PROVINCE, PAKISTAN. - Gada Hussain Brohi; Nadir Ali Birmani (Journal of Animal and Plant Sciences, 2023)
Present study aimed to investigate Cestode fauna of avian host Little Cormorant, Microcarbo niger captured from Kamber-Shahdadkot district, Sindh province of Pakistan. Eight Little Cormorant Microcarbo niger hosts were investigated for the presence of Cestode parasites. Anesthetized birds were dissected and entire alimentary canal and associated organs were removed. A total of five specimens of Dilepidid Cestodes were recovered from the intestine of three hosts. Cestodes collected from the freshly dissected hosts were initially placed in saline solution and dehydrated in graded series of ethanol, stained with borax carmine, cleared in clove oil and xylene and finally mounted in Canada balsam permanently. Parasitic examination revealed an apparently undescribed species of genus Dilepis Weniland, 1858 from the intestine of the host, M. niger. Recovered specimens differ remarkably from other known species of genus Dilepis Weniland, 1858 in having some unique features such as, 12 rostellar hooks, long neck, four pre-ovarian testes, unilateral genital pore and spinose cirrus sac located at lower part of each segment. On the basis of the above morphometric variations, but absence of molecular study, present specimens are identified as Dilepis sp. This paper also constitutes the first record of the genus Dilepis Weinland, 1958 from Pakistan.
Keywords: Avian Cestode; Dilepis Weniland; 1858; Little Cormorant Microcarbo niger; Sindh; Pakistan